Evaluation of Demographic and Clinical Presentation of Colorectal Carcinoma in Rajshahi Region (TAJ: Journal of Teachers Association, 2020)
This cross-sectional, descriptive, observational study was carried out for a period of 24 months from January 2014 to December 2015 in the Department of Pathology and Department of Surgery, Rajshahi Medical College, Rajshahi for evaluation of clinical and histological presentation of colorectal carcinoma patients in total fifty four patient. Data were collected by face to face interview, clinical examination. The study revealed that the colorectal carcinoma was highest in the 5th and 6th decade and rectal area (46.3%) and male predominance was observed with male to female ratio being 3:2. Abdominal pain (61.1%), weight loss (61.1%), per rectal bleeding (57.4%), altered bowel habit (24.1%) and melena (24.1%) are the main presenting symptoms. In terms of ABO blood grouping, blood group ‘B’ was found predominant (44.4%), followed by group ‘A’ (24.1%), group ‘AB’ (14.8%) and group ‘O’ (16.7%).TAJ 2020; 33(2): 15-19